A construção discursiva da sustentabilidade urbana na Microrregião de Garanhuns - PE - Ferreira, Márcio Rosseline da Silva (2013)
With the environmental crisis bequeathed by the contradictions arising from instrumental rationality both as regards their technical and scientific as in its economic aspect, this spectrum has emerged a discourse marker of environmental sustainability according to the parameters set by a "paradigm" guided by a social conception environmental rationality. Thus, social policies instituted from this framework of rationality, began to consider the importance of environmental issues in its constitution as a public policy. Thus, in order to contribute to a discourse analysis of public policies in the urban environment, this research aimed to examine the discursive formation of urban sustainability in Microregion Garanhuns through research developed with the main cities of the aforementioned micro. The "object" of selected search meets the requirements of the City Statute (2001) regarding the implementation of a sustainable urban policy. These municipalities have approximately 210 thousand inhabitants, or nearly half the population of Microregion Garanhuns. These counties are characterized by greater rate of urban population in relation to the rate of rural population (89% Garanhuns, Bom Conselho 65% and Lajedo 74%) (CONDEPE / FIDEM, 2010) in comparison with others. However, another important criterion for scientific research, in addition to the demographic factor was logistical. Well, it derives both the attraction of economic enterprises as the environmental impacts of the first. However, research finds possible fragmentation of the discourse on urban public policy considering sectorization management in government, contributing to the construction of a discourse eminentemete administrative and technocratic nature, incompatibilizando with the official discourse found mainly in the letters of legal authority. The interdependence of urban sustainability to sustainability policy rendered in legal discourse aimed sustainable cities, is represented in the design of municipal councils, however, the obstacles arising from practices of government, unfeasible the empowerment of civil society in environmental discourse of social control urban.